THE EFFECT OF DIGITAL COMMUNICATION AND WORK BOREDOM ON THE WORK CREATIVITY OF CIVIL SERVANTS - Asih Niati; Teguh Ariefiantoro; Edy Suryawardana (LPSDI Bina Patria, 2023)
The existence of a policy of implementing work without being in the office has become a new work order that forces companies to do work variations. The emergence of the extraordinary events has changed the perspective of work activities to be more responsive and adaptive to changes by implementing WFH (Work From Home) and remain productive. However, restrictions on movement to explore and exploit in carrying out work activities become obstacle for the employees in giving maximum contribution to the company. Likewise with civil servants who are required to do their work activities at home. These new work activities indirectly have an impact on well-being that interferes emotionally with time and builds the employees’ boredom in carrying out work which can ultimately reduce their work creativity. This study aims to explore the effect of digital communication and work boredom on the work creativity of civil servants. This research method is conducted through the distribution of questionnaires using the Structural Equation Modeling (SEM) method and using the Analysis Moment of Structural (AMOS) version 21.0 program, as the analytical tool. The results of the study indicate that Digital Communication has no effects on Work Boredom. Likewise, work boredom has no effects on the employees’ creativity. However, digital communication has effects on the employees’ creativity.